Injection molding austenitic stainless steel with high wear resistance and high plasticity

By controlling the Mo element content in austenitic stainless steel and using injection molding process combined with sintering, solid solution and aging treatment, the shortcomings of austenitic stainless steel in wear resistance and plasticity are solved, and the hardness and corrosion resistance are improved, which is suitable for a wider range of application fields.

CN119710486APending Publication Date: 2025-03-28HUNAN HENGJI POWDER TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411982629.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing austenitic stainless steels have shortcomings in wear resistance and plasticity, which limits their use in certain applications.

Method used

By controlling the Mo element content in austenitic stainless steel, optimizing its composition, using injection molding technology and combining sintering, solid solution and aging treatment, austenitic stainless steel with high wear resistance and high plasticity is obtained.

Benefits of technology

The hardness of austenitic stainless steel is achieved at more than 200HV, with an elongation of more than 40%, and has high corrosion resistance, which is suitable for a wider range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710486A_ABST
    Figure CN119710486A_ABST
Patent Text Reader

Abstract

The invention discloses injection molding austenitic stainless steel with both high wear resistance and high plasticity, the injection molding austenitic stainless steel comprises the following components in percentage by mass: 5-7% of Mo, 12-14% of Ni, 0.05-0.15% of O, 22-23% of Cr, less than or equal to 0.03% of C, less than or equal to 2% of Mn, less than or equal to 0.50% of Si, less than or equal to 0.3% of Nb and the balance of ferrum, and the injection molding austenitic stainless steel is prepared by controlling the element content and a heat treatment process. And through a proper heat treatment process, a product with very high wear resistance (the hardness exceeds 250 HV) and the ductility higher than 40% can be obtained, and the corrosion resistance is superior to that of traditional stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials, and in particular relates to an injection-molded austenitic stainless steel with high wear resistance and high plasticity. Background Art

[0002] Austenitic stainless steel has excellent properties such as non-magnetic, corrosion-resistant, easy to recycle, and low cost, and is widely used in military, medical, civilian and other fields. Metal injection molding, due to its unique technical advantages, provides a new idea for the preparation of small and complex austenitic stainless steel samples. It has now developed into one of the most important technologies in the production of austenitic stainless steel parts. Among them, the most widely used austenitic stainless steels include 316L and 304 stainless steels.

[0003] 304 austenitic stainless steel is widely used in household products, auto parts, medical equipment, ship parts and other fields due to its excellent physical properties, mechanical properties and corrosion resistance. 316L adds a certain amount of Mo element compared to 304, and the content of Cr element is also increased to a certain extent. It is often used in highly corrosive environments and plays an important role in aerospace, petroleum, chemical, medicine, transportation, electronics and other fields. However, the wear resistance of these two stainless steels is poor, which limits their application areas.

[0004] To overcome this defect, researchers have developed super austenitic stainless steel, which has the characteristics of high alloying (high content of Cr and Mo elements), and can effectively improve mechanical properties and corrosion resistance. Among them, 254SMO stainless steel can form a dense oxide film on the surface due to its high content of chromium and molybdenum elements, which effectively resists chemical erosion such as oxidation and corrosion, and can withstand high pressure and impact, and has good mechanical properties. However, 254SMO stainless steel contains certain carbon and nitrogen elements, which are difficult to accurately control through the sintering process. Therefore, it is necessary to develop austenitic stainless steel that is more suitable for powder metallurgy.

[0005] At present, injection molding is an advanced molding method for preparing large quantities of parts with complex shapes. The process is to evenly mix solid powder with organic binder, inject it into the mold cavity with an injection molding machine under heated plasticization state after granulation, and then remove the binder in the molded blank by chemical or thermal decomposition method, and finally obtain the final product after sintering and densification. The advantages of injection molding can minimize the segregation of alloy components and eliminate the inhomogeneity of cast structure. It can also achieve near-net forming and automated mass production, effectively reducing the consumption of production resources and energy, and can also produce materials and products with special structures and properties. The application fields of injection molding technology are very wide, mainly including automobiles, aerospace, electronics, medical devices and other fields. Take the fields of automobiles and medical devices as examples: in the automotive field, this technology can manufacture high-strength, wear-resistant, and corrosion-resistant engine parts, gearbox gears, etc.; in the field of medical devices, this technology can manufacture high-precision, non-toxic, and sterile artificial joints, dental implants, etc.

[0006] In addition, austenitic stainless steel generally has a high plasticity (≥20%). Although adding alloying elements can enhance the hardness, it will rapidly deteriorate the plasticity to below 10%. Therefore, ordinary austenitic stainless steel often has good plasticity, but low hardness and poor wear resistance. For example, the hardness of traditional 316L austenitic stainless steel is only 140-160HV. Some patents use alloying methods to strengthen the alloy so that the alloy hardness can reach more than 200HV. CN202410097013.9 discloses a niobium-cerium composite-reinforced austenitic stainless steel and a preparation method thereof. Niobium-cerium elements are used to strengthen austenitic stainless steel so that its hardness reaches 210-230HV. CN202311793116.0 discloses a corrosion-resistant and tough austenitic stainless steel and a preparation method thereof. By adding a certain amount of Mg, Ti, and Zr to the stainless steel matrix, a stainless steel with a tensile strength of 545MPa and a yield strength exceeding 250MPa is obtained. CN202311495005.1 discloses an easy-to-sinter high-hardness austenitic stainless steel powder for injection molding and its application to obtain a stainless steel with a hardness of about 215HV, but the invention requires the addition of carbon in the form of graphite, and it is difficult to accurately control the content of carbon during degreasing and sintering, resulting in unstable performance of the alloy, and the hardness is still far below 250HV. Therefore, it is urgent to develop an injection molding austenitic stainless steel with both high wear resistance and high plasticity. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an injection molded austenitic stainless steel with high wear resistance and high plasticity, and to optimize the performance of the austenitic stainless steel by controlling the content of the Mo element in the austenitic stainless steel, so as to obtain injection molded austenitic stainless steel with a wider application environment.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The invention discloses an injection-molded austenitic stainless steel with high wear resistance and high plasticity. The injection-molded austenitic stainless steel has the following components, calculated by mass percentage: 5-7% Mo, 12-14% Ni, 0.05%-0.15% O, 22-23% Cr, C≤0.03%, Mn≤2%, Si≤0.50%, Nb≤0.3%, and the balance is iron.

[0010] In a preferred embodiment, the injection molded austenitic stainless steel has the following composition, by mass percentage: Mo 5-7%, Ni 12-13.5%, O 0.05%-0.15%, Cr 22.40-22.60%, C≤0.03%, Mn≤2%, Si≤0.50%, Nb≤0.3%, and the balance is iron.

[0011] Further preferably, the injection molded austenitic stainless steel has the following composition, by mass percentage: Mo 5.5-6.7%, Ni 12.5-13.5%, O 0.05-0.12%, Cr 22.40-22.60%, C 0.004-0.006%, Mn 0.35-0.45%, Si 0.25-0.4%, Nb 0.26-0.28%, and the balance is iron.

[0012] In a preferred embodiment, the injection molded austenitic stainless steel is obtained by kneading austenitic stainless steel powder, injection molding, catalytic degreasing to obtain a degreased blank, sintering the degreased blank under a protective atmosphere, and finally solution treating the degreased blank.

[0013] Further preferably, the sintering is carried out under a protective atmosphere, the sintering temperature is 1250-1350°C, and the sintering time is 2-4 hours. The austenitic stainless steel obtained by sintering at 1250-1350°C for 3 hours has a density of 7.80-8.00 g / cm 3 , elongation is 20-25%, and tensile strength is 300-500MPa.

[0014] In a preferred embodiment, the temperature of the solution treatment is 1000-1300° C., and the time of the solution treatment is 0.5-6 h, preferably 3-5 h.

[0015] By improving uniformity and performance through solid solution treatment, an elongation of 39% to 48% can be obtained after solid solution treatment of the austenitic stainless steel at 1200°C for 0.5 to 6 hours.

[0016] The inventors found that the corrosion resistance of samples with short solution treatment time is poor. The samples with short insulation time form a certain amount of delta ferrite. This phase is enriched with Cr elements, which will reduce the corrosion resistance of the material. As the insulation time increases, the phase dissolves in the matrix, the material composition is uniform, and the corrosion resistance is improved. The sample with insulation for 4 hours is a fully austenitic structure with high corrosion resistance. At room temperature (25°C), the solution-treated stainless steel sample was pre-immersed in a 3.5% NaCl solution for 1 hour. After the equivalent circuit fitting of EIS (electrochemical impedance spectroscopy), it was found that the Rct value of the stainless steel after solution treatment was 280-700 kΩcm 2 Compared with the traditional 316L stainless steel, its Rct value is larger (184kΩcm 2 ), indicating that the corrosion resistance of the stainless steel of the present invention is much higher than that of ordinary 316L stainless steel.

[0017] In a preferred embodiment, the austenitic stainless steel obtained after the solution treatment is subjected to an aging treatment, wherein the aging treatment temperature is 800 to 1100° C. and the aging treatment time is 3 to 5 hours.

[0018] After the solutionized sample was aged at 950℃ for 4h, the friction coefficient was tested to obtain a coefficient curve with a fluctuation range of 0.55 to 0.70:

[0019] a. When the addition amount of Mo is 5.5%, after solution treatment at 1200℃ for 0.5 to 6 hours, an elongation of 41 to 44% can be obtained, and after solution treatment for 2 to 6 hours, a tensile strength of 499 to 612 MPa and a yield strength of 270 to 358 MPa can be obtained. After aging at 950℃ for 4 hours, the sample is tested by a HT-1000 friction and wear testing machine, and a curve is obtained in which the friction coefficient remains in the fluctuation range of 0.70 within 30 minutes.

[0020] b. When the addition amount of Mo is 6%, after solution treatment at 1200℃ for 0.5 to 6h, an elongation of 39 to 42% can be obtained, and after solution treatment for 2 to 6h, a tensile strength of 604 to 652MPa and a yield strength of 324 to 356MPa can be obtained. After aging at 950℃ for 4h, the sample is tested by HT-1000 friction and wear testing machine, and a curve is obtained in which the friction coefficient remains in the fluctuation range of 0.60 within 30min.

[0021] c. When the addition amount of Mo is 6.5%, after solution treatment at 1200℃ for 0.5 to 6 hours, an elongation of 36 to 39% can be obtained, and after solution treatment for 2 to 6 hours, a tensile strength of 636 to 785 MPa and a yield strength of 342 to 394 MPa can be obtained. After aging at 950℃ for 4 hours, the sample is tested by a HT-1000 friction and wear testing machine, and a curve is obtained in which the friction coefficient remains in the fluctuation range of 0.55 within 30 minutes.

[0022] Principles and advantages

[0023] The addition of a small amount of Nb element in the present invention can better control the sintering process and improve the mechanical properties of the 316Mo alloy. One of the most important functions of niobium is to react with carbon to form stable niobium carbide (NbC). The formation of this carbide helps to capture carbon in the alloy and reduce the chance of carbon reacting with chromium to form chromium carbide (Cr23C6). The formation of chromium carbide will cause the chromium content near the grain boundary to decrease, thereby causing intergranular corrosion. By forming niobium carbide, niobium helps to prevent dechromization of the grain boundary, thereby improving the alloy's resistance to intergranular corrosion. At the same time, niobium can form a eutectic liquid phase (1360°C) in the alloy, exist as a solid solution in the lattice of austenitic steel, increase the degree of distortion of the lattice, increase the resistance to the movement of dislocations, and strengthen the mechanical properties of the alloy.

[0024] The alloy powder of the present invention adopts carbon-free sintering to reduce the formation of carbides and improve the stability and controllability of the process. Specifically, carbon powder reacts with other elements such as Cr at high temperatures. Carbon reacts with chromium in austenitic stainless steel to form chromium carbide, which may cause local dechromization and enhance the intergranular corrosion tendency of the material. Carbon-free or low-carbon structures can effectively reduce the formation of chromium carbide, thereby enhancing the overall corrosion resistance of the material. In addition, excessive carbon powder may cause changes in the physical properties of the alloy such as the melting point and fluidity, which increases the difficulty of controlling the alloy molding.

[0025] The sintered sample of the present invention has a large number of blocky grain boundaries, and the grain boundaries are in a network structure. After the solution treatment, a large number of micro-regions with high Cr and Mo element contents appear at the grain boundaries. A large number of dislocations in the grain boundary positions of the sample cannot cross these regions, resulting in the formation of dislocation cells. These regions hinder the movement of dislocations, causing dislocation accumulation, effectively strengthening the grain boundaries of the sample, and the sample grains are prone to form nano twins under stress. A large number of such structures are found in almost every grain, strengthening the austenite matrix.

[0026] After aging treatment, it was found that there were many precipitates at the grain boundaries of the samples. The number and coverage area of ​​the precipitated phase were similar to those of the solution treated samples, but the precipitated phase at the grain boundaries mainly showed a network structure, and the contrast was significantly different from the matrix. The precipitated phase was σ phase. The large amount of precipitation of the strengthening phase increased the hardness and strength of the stainless steel after aging treatment, but the elongation of the stainless steel also decreased.

[0027] The present invention greatly improves the mechanical properties of injection molded austenitic stainless steel by regulating the content of alloy elements, so that the hardness reaches above 200 HV while having excellent high wear resistance, an elongation of more than 40%, and high corrosion resistance.

[0028] The present invention greatly improves the mechanical properties of injection molded austenitic stainless steel by high alloying Mo, making it have excellent wear resistance, and still have an elongation of about 40%, and also have better corrosion resistance than traditional stainless steel (such as 316L). Compared with traditional stainless steel, the stainless steel of the present invention can obtain high density at a lower sintering temperature and a wider sintering range, and has a wide range of applications in more fields.

[0029] Specifically, in the surgical instruments of medical equipment, such as scalpels and surgical forceps, the high hardness and high strength of the stainless steel of the present invention make the service performance better and the application range wider. At the same time, its corrosion resistance can effectively resist the corrosion of corrosive media such as body fluids and disinfectants, ensuring the sanitation and safety of surgical instruments. In addition, in implants, such as bone screws and bone plates, these implants need to work in the human body for a long time, so their corrosion resistance and biocompatibility are extremely high. This project can meet these needs.

[0030] In marine engineering structural parts in the field of marine applications, such as the support structure of offshore platforms, joints of marine pipelines, etc., these structures are subject to long-term erosion by seawater and impact by waves, so the materials need to have extremely high corrosion resistance and strength. The stainless steel of the present invention is an ideal material to meet these requirements. At the same time, in the field of ship parts application, such as propellers, anchor chains, etc., these parts need to withstand corrosion and mechanical wear from seawater. The high wear resistance and high strength of the stainless steel of the present invention can ensure the long-term stable operation of these parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The mechanical properties of solution treated 316Mo(x) stainless steel are shown in Figure 1. (a) is a stress-strain curve; (b) is a tensile property curve. The fracture surfaces of the solution treated 316Mo(x) stainless steel sintered samples of the three embodiments are all dimples, showing ductile fracture.

[0032] Figure 2 The scanning electron microscope (SEM) morphology of the austenitic stainless steel provided in Example 1 is shown in FIG. (a) is the SEM morphology of the sample after sintering, (b) is the SEM morphology of the sample after solution treatment, and (c) is the SEM morphology of the sample after aging.

[0033] As can be seen from the figure, a large number of blocky grain boundaries appear in the sintered samples, and the grain boundaries present a network structure (such as Figure 2As shown). After solution treatment, a large number of micro-regions with high Cr and Mo content appear at the grain boundaries. A large number of dislocations in the sample grain boundary position cannot cross these areas, resulting in the formation of dislocation cells. These areas hinder dislocation movement, causing dislocation accumulation, effectively strengthening the sample grain boundaries. Nano twins are easily formed under stress in the sample grains. A large number of such structures are found in almost every grain, strengthening the austenite matrix. After aging treatment, it was found that there were more precipitates at the grain boundaries of the sample. The number and coverage area of ​​the precipitated phase were similar to those of the solution treatment sample, but the precipitated phase at the grain boundary was mainly a network structure, and the contrast was significantly different from the matrix. The precipitated phase was σ phase. The large amount of precipitation of the strengthening phase increased the hardness and strength of the stainless steel after aging treatment, but the elongation of the stainless steel also decreased.

[0034] Figure 3 Wear morphology of three different 316Mo stainless steels after aging at 950℃ for 4h, scanned by scanning electron microscope (SEM), a for 316Mo(5.5), b for 316Mo(6.0), and c for 316Mo(6.5). The three austenitic stainless steels with different molybdenum contents all have good wear resistance, among which 316Mo(6.5) has the best wear resistance, the lowest friction coefficient, and the best wear resistance. DETAILED DESCRIPTION

[0035] Embodiment 1:

[0036] 316Mo (5.5) austenitic stainless steel, powdered by gas atomization, powder composition: 0.006% C, 0.41% Mn, 0.38% Si, 0.27% Nb, 22.60% Cr, 0.115% O, 12.88% Ni, 5.69% Mo and the balance of iron, powder size D 10 =4.43μm, D 50 =11.41μm, D 90 =23.66μm. The stainless steel sample was prepared according to the powder metallurgy injection molding process (using the same process as CN202311495005.1 for injection molding and catalytic degreasing), and then sintered in an argon atmosphere at a sintering temperature of 1340°C for 3h. The density of the 316Mo (5.5) stainless steel obtained after sintering was 7.98g / cm 3, hardness is 248.56±4.12HV, tensile strength is 417.89MPa, yield strength is 221.98MPa, and elongation is 25.27±0.94%. After solution treatment at 1200℃ for 4h, the hardness reached 253.62±2.19HV, tensile strength reached 612.14MPa, yield strength reached 358.94MPa, and elongation reached 44.27±0.67%. After aging at 950℃ for 4h, the sample was tested by HT-1000 friction and wear testing machine, and the curve of friction coefficient fluctuating within 0.70 within 30min was obtained. Corrosion resistance Rct is 503.90kΩcm 2 .

[0037] Embodiment 2:

[0038] 316Mo (6.0) austenitic stainless steel, powdered by gas atomization, powder composition: 0.004% C, 0.38% Mn, 0.28% Si, 0.28% Nb, 22.57% Cr, 0.057% O, 12.83% Ni, 6.06% Mo and the balance of iron, powder size D 10 =5.38μm, D 50 =12.11μm, D 90 =25.65μm. The stainless steel sample was prepared according to the powder metallurgy injection molding process, with a sintering temperature of 1300℃ and a sintering time of 3h. The density of 316Mo(6.0) stainless steel obtained after sintering was 8.00g / cm 3 , hardness is 255.74±4.36HV, tensile strength is 465.37MPa, yield strength is 258.74MPa, and elongation is 22.56±0.56%. After solution treatment at 1200℃ for 4h, the hardness reached 265.64±2.06HV, tensile strength reached 652.94MPa, yield strength reached 365.22MPa, and elongation reached 42.40±0.32%. After aging at 950℃ for 4h, the sample was tested by HT-1000 friction and wear testing machine, and the curve of friction coefficient fluctuating within 0.60 within 30min was obtained. Corrosion resistance Rct is 556.50kΩcm 2 .

[0039] Embodiment 3:

[0040] 316Mo (6.5) austenitic stainless steel, powdered by gas atomization, powder composition: 0.006% C, 0.39% Mn, 0.26% Si, 0.26% Nb, 22.47% Cr, 0.1% O, 13.02% Ni, 6.63% Mo and the balance of iron, powder size D 10 =3.96μm, D 50=13.12μm, D 90 =24.23μm. The stainless steel sample was prepared according to the powder metallurgy injection molding process, with a sintering temperature of 1250℃ and a sintering time of 3h. The density of 316Mo(6.5) stainless steel obtained after sintering was 7.82g / cm 3 , hardness is 267.26±2.35HV, tensile strength is 517.89MPa, yield strength is 289.67MPa, and elongation is 20.28±0.64%. After solution treatment at 1200℃ for 4h, the hardness reached 291.16±3.96HV, tensile strength reached 688.31MPa, yield strength reached 389.62MPa, and elongation reached 34.27±0.37%. After aging at 950℃ for 4h, the sample was tested by HT-1000 friction and wear testing machine, and the curve with friction coefficient fluctuating within 0.55 within 30min was obtained. Corrosion resistance Rct is 704.20kΩcm 2 .

[0041] From the above examples 1, 2, and 3, it can be seen that the injection molded austenitic stainless steel of the present invention has different optimal sintering temperatures corresponding to different Mo contents, and has a wider sintering temperature range to obtain a higher density, and its hardness and mechanical properties are better. Secondly, the three austenitic stainless steels with different Mo contents have the best mechanical properties at 1200℃ for 4h, among which 316Mo (6.0) has the most excellent mechanical properties.

[0042] Comparative Example 1:

[0043] The other conditions of this comparative example are the same as those of Example 1, except that no aging treatment is performed. After the solid solution treatment, the hardness of the 316Mo austenitic stainless steel reaches 265.64±2.06HV, the tensile strength reaches 652.94MPa, the yield strength reaches 365.22MPa, and the elongation reaches 42.40±0.32%. The corrosion resistance Rct is only 260.50kΩcm 2 .

[0044] After the solution treatment, the hardness, tensile strength and yield strength of the 316Mo austenitic stainless steel do not change much, but the corrosion resistance is greatly reduced. This shows that aging strengthening has a great improvement on the corrosion resistance of the stainless steel of the present invention.

[0045] Comparative Example 2

[0046] The other conditions of this comparative example are the same as those of Example 2, except that the solution treatment time is changed to 0.5 h. After solution treatment, the hardness of 316Mo austenitic stainless steel is 198.78 ± 3.58 HV, the tensile strength is 352.16 MPa, the yield strength is 168.32 MPa, and the elongation is 41.28 ± 2.82%. After testing the sample with the HT-1000 friction and wear tester, a curve is obtained in which the friction coefficient fluctuates within the range of 1.0 within 30 min.

[0047] It can be found that the tensile strength, yield strength and wear resistance of 316Mo (6.0) stainless steel after solution treatment for 0.5h are greatly reduced, and only its hardness is improved to a certain extent. The mechanical properties of 316Mo (6.0) stainless steel after solution treatment for 0.5h cannot meet the performance required by the present invention.

Claims

1. An injection molded austenitic stainless steel with high wear resistance and high plasticity, characterized in that: The injection molded austenitic stainless steel has the following composition by mass percentage: Mo 5-7%, Ni 12-14%, O 0.05%-0.15%, Cr 22-23%, C≤0.03%, Mn≤2%, Si≤0.50%, Nb≤0.3%, and the balance is iron.

2. The injection molded austenitic stainless steel with high wear resistance and high plasticity according to claim 1, characterized in that: The injection molded austenitic stainless steel has the following composition by mass percentage: Mo 5-7%, Ni 12-13.5%, O 0.05%-0.15%, Cr 22.40-22.60%, C≤0.03%, Mn≤2%, Si≤0.50%, Nb≤0.3%, and the balance is iron.

3. The injection molded austenitic stainless steel with high wear resistance and high plasticity according to claim 1 or 2, characterized in that: The injection molded austenitic stainless steel has the following composition by mass percentage: Mo 5.5-6.7%, Ni 12.5-13.5%, O 0.05-0.12%, Cr 22.40-22.60%, C 0.004-0.006%, Mn 0.35-0.45%, Si 0.25-0.4%, Nb 0.26-0.28%, and the balance is iron.

4. The injection molded austenitic stainless steel with high wear resistance and high plasticity according to claim 1 or 2, characterized in that: The injection molded austenitic stainless steel is obtained by mixing austenitic stainless steel powder, then subjecting it to injection molding and catalytic degreasing to obtain a degreased blank, sintering the degreased blank under a protective atmosphere, and finally subjecting it to a solid solution treatment.

5. The injection molded austenitic stainless steel with high wear resistance and high plasticity according to claim 4, characterized in that: The sintering is carried out under a protective atmosphere, the sintering temperature is 1250-1350° C., and the sintering time is 2-4 hours.

6. The injection molded austenitic stainless steel with high wear resistance and high plasticity according to claim 4, characterized in that: The temperature of the solution treatment is 1000-1300° C., and the time of the solution treatment is 0.5-6 hours.

7. The injection molded austenitic stainless steel with high wear resistance and high plasticity according to claim 4, characterized in that: The austenitic stainless steel obtained after the solution treatment is subjected to an aging treatment, wherein the aging treatment temperature is 800 to 1100° C. and the aging treatment time is 3 to 5 hours.

Citation Information

Patent Citations

  • Easily-sintered high-hardness austenitic stainless steel powder for injection molding and application thereof

    CN117551942A

  • Corrosion-resistant high-toughness austenitic stainless steel and preparation method thereof

    CN117737612A

  • Niobium-cerium composite reinforced austenitic stainless steel and preparation method thereof

    CN117867395A